RETRACTED: Climate Change Impacts and Adaptation Strategies on Tourism in Nepal - Bhandari, Lekha Nath (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Retraction Notice: The editors have retracted this article "Climate Change Impacts and Adaptation Strategies on Tourism in Nepal" due to a high level of plagiarism from the article Nyaupane, Gyan P. and Chhetri, Netra (2009) 'Vulnerability to Climate Change of Nature-Based Tourism in the Nepalese Himalayas', Tourism Geographies, 11: 1, 95-119. https://doi.org/10.1080/14616680802643359